Social media addiction and stress among indonesian medical students in Banjarmasin - Aldiya Jamila; Dwi Setyohadi; Sherly Limantara; Pagan Pambudi; Oski Illiandri (Universitas Syiah Kuala, 2021)
It has been known that some medical student has a high level of stress because of its academic burden. If it could not be well managed this will lead the student to bad academic achievement and academic failure. Many early student monitoring tool has been used to prevent student academic failure, however, there was no satisfying tool until its getting worse into academic failure. An academic supervisor needs to find a new tool to screen the stress level of a medical student at an early stage. Nowadays, social media can not be separated from student life. Some students had high social media activity and some not. Recent studies report that social media activity can reflect one’s mental health. However, the relation between social media addiction and mental health among medical students is still unknown. This study aimed to find a relation between student social media intensity and level of neuroticism in medical students. This study used a cross-sectional approach, conducted on eighty-four students in medical school. Social Networking Time Use Scale (SONTUS) has been used to measure social media activity and Depression, Anxiety, and Stress Scale (DASS) was used to measure mental health. Data analyzed using the Spearman test. The results showed that 35.7% of respondents used social media with low intensity, 51.1% moderate intensity, 12% high intensity, and 1.2% very high intensity. The rate of depressive symptoms in 63% of respondents was in the normal range, 14.3% mild, 15.5% moderate, 4.8% severe, and 2.4% very severe. The level of anxiety symptoms in 31% of respondents was in the normal range, 12% mild, 29.8% moderate, 14.3% severe, and 13.1% very severe. The correlation between the intensity of social media use and the level of depressive symptoms is not significant (p=0.109; r=0.136), but significant with the level of anxiety symptoms (p=0.013; r=0.241). Base on the result, it was concluded that social media addiction is related to the high level of stress type of anxiety but not depression. Further research needs to be conducted with a more subject sample.